ChemInform Abstract: Synthesis of Substituted Dibenz[a, c]anthracenes and an Investigation of Their Liquid‐Crystalline Properties. Issue 26 (June 2015) - Psutka, Katie M.; Williams, Joshua; Paquette, Joseph A.; Calderon, Oliver; Bozek, Kevin J. A.; Williams, Vance E.; Maly, Kenneth E.
Abstract Suzuki coupling of dibromonaphthalenes and boronate esters followed by oxidative cyclization leads to dibenzanthracene derivatives.